Pet feeder with NodeMCU using mobile application - Muhammad Sodiq Amin, Mohamd Isa (2018)
Nowadays, pets are considered as a life companion. However, managing pets sometimes is such a nuisance task for the owner especially when no one is at home. Most pet owners cannot stay at home every time to feed their pet regularly, yet their pets need to be fed throughout the day. Therefore, with a development of Pet Feeder with NodeMCU using Mobile Application will overcome this problem, this system will assist and allow owner to remotely feed their pets at a specific time without having to present at the feeding location. Iterative Waterfall method has been used to develop this system. This method is divided into four phases starting from Requirement Analysis, Design, Implementation and Testing. Iterative waterfall methodology will produce software that works quickly and early in the life cycle software. Next, pets can have their food without the present of owners while owners can enjoy works and travelling without having worries about feeding their pets. This project has been successfully developed which enable owners to feed their pets remotely away from home and pets gets food at the right time.